The effect of intergroup threat and social identity salience on the belief in conspiracy theories over terrorism in Indonesia: Collective angst as a mediator - Mashuri, Ali (Colombia: University of San Buenaventura, 2015)
The present study tested how intergroup threat (high versus low) and social identity as a Muslim (salient versus non-salient) affected belief in conspiracy theories. Data among Indonesian Muslim students (N= 139) from this study demonstrated that intergroup threat and social identity salience interacted to influence belief in conspiracy theories. High intergroup threat triggered greater belief in conspiracy theories than low intergroup threat, more prominently in the condition in which participants' Muslim identity was made salient. Collective angst also proved to mediate the effect of intergroup threat on the belief. However, in line with the prediction, evidence of this mediation effect of collective angst was only on the salient social identity condition. Discussions on these research findings build on both theoretical and practical implications.